Effectiveness of adjunctive ultrasound after mammography in improving breast cancer screening findings from a study in Malaysian women - Mohamed Ibrahim Wahid,; Azmi, Nurul Alia; Pei Yun Tan,; Chen, Bao Jing (Asian Journal of Medical Sciences, 2024)
Background: Breast cancer is a significant health issue affecting women worldwide, including Malaysia, where the incidence of breast cancer is increasing. Early detection of breast cancer plays a crucial role in improving treatment outcomes and reducing mortality rates. Aims and Objectives: This study examines the impact of adjunctive breast ultrasound (BUS) on screening for Malaysian women, offering evidence to enhance future protocols and decisions in the early detection. Materials and Methods: This study involved 5807 women aged 40 and above undergoing breast screening at Beacon Hospital from January to December 2022. Data collected included mammography and BUS results, categorized by breast imaging reporting and data system (BI-RADS) and diagnostic criteria. Suspicious cases on both modalities had histopathology examination (HPE) for confirmation. A subset of 1690 cases underwent both mammography and BUS screening and was compared to those who only had mammography using BI-RADS scores. Results: This study revealed that the majority of mammograms, 94.69% (5499 cases), were categorized as BI-RADS category 0, 1, 2, and 3, while 5.3% (307 cases) were classified as BI-RADS 4 and 5. Among the cases that underwent ultrasound (1688 cases), 23.43% of them were categorized as BI-RADS 4–5. Using ultrasound in addition to mammography increased the number of cases (BI-RADS 4–5) by 33.48%, resulting in a total of 460 cases identified compared to 307 cases, detected by mammography alone. Significantly, 39% (74 cases) of the 190 cases with confirmed malignancies (BI-RADS 6) by HPE were initially classified as negative mammography (BI-RADS 0–3) but were later identified as BI-RADS 5 on ultrasound. Conclusion: Ultrasound as a supplementary screening method holds the potential for boosting breast cancer detection sensitivity and reducing false negatives, thereby aiding in early detection and better treatment outcomes.